Development of Education in Siberia in First Quarter of 18th Century - E. V. Kostetskaya; L. N. Suslova (Научный диалог)
The article is devoted to the study of the schooling formation on the territory of the Siberian province in the first quarter of the 18th century. The process of origin and development of spiritual and secular education in Siberia is characterized. The study was carried out on the basis of an analysis of the decrees of Peter I published in the Complete Collection of Laws of the Russian Empire, which regulate the organization of educational institutions in Siberia. A number of clerical sources of the Russian State Archive of Ancient Acts, in particular, the cases of the Siberian Order, are analyzed. Also, to study the topic, materials from the newspaper “Tobolsk Gubernskie Vedomosti” were involved. The authors of the article show that Peter’s modernization processes in the field of education were reflected in the life of the Siberian province in the first quarter of the 18th century. It is concluded that the main changes that affected the field of education are associated with the implementation of the reforms of Peter I. The role of the first theological schools in the education system of the Siberian province, the significance of the decrees of Peter I and the activities of the Orthodox Church in their formation are considered. At the same time, it is proved that the political events and cultural innovations of the Petrine era contributed to the formation of secular education and the spread of enlightenment among Siberians.